Zaburzenia semantyki frazeologizmów u osób w łagodnej fazie otępienia alzheimerowskiego. Wstępne wyniki badań - Antczak-Kujawin, Justyna (Teoria i praktyka logopedyczna. Wybrane zagadnienia, 2018)
The author of this article discusses the issue of defrazeologization in dementia, it means the disruptions in realization of phrasal idioms in people with early stage Alzheimer’s dementia, which manifest in transformations of their formal structure (modifying innovations) and the semantic structure (semantic modifications). These phraseological innovations should be interpreted as the unconscious modifications resulting from the progressive cognitive dysfunctions of people with dementia. The author of this work presents the preliminary results of research conducted in 2015–2017 on the group of 15 people with early stage Alzheimer’s dementia with application of authorial test of lexical and semantic skills in elderly people with dementia.